Effect of butyrate glycerine on diesel engine performance and emission characteristics - Muhammad Ammar Asyraf, Bin Zainuddin (Universiti Malaysia Sarawak (UNIMAS), 2017)
The aim of this project is to study the effect of butyrate glycerine on engine performance and exhaust emission. Exhaust emission of diesel engine consist of Carbon Monoxide (CO), Oxides of Nitrogen (NOx) and Particulate Matter (PM). The disadvantages of diesel engine are they produce CO emission, NOx emission and PM emission. These exhaust emissions are one of the contribution of air pollution, global warming and hence reduce the air quality. This final year project discusses on diesel engine performance and emission characteristics of compression ignition diesel engine operating on diesel fuel blend which is 10% by weight of butyrate glycerine. In order to investigate the factor which affects the engine performance and emission characteristics, the experiment is conducted at an engine speed of 1200, 1700 and 2200 RPM and the tailpipe exhaust emissions were measured using flue gas analyzer and smoke meter. The NOx and CO emission shows inconsistent reading as the engine speed is increased. However, the NOx and CO emission value is decreasing as compared to the benchmark reading. The PM emission value is decreasing as the engine speed is increasing.